Regioselectivity of the SEAr-based cyclizations and SEAr-terminated annulations of 3,5-unsubstituted, 4-substituted indoles - Das, Jonali; Das, Sajal Kumar (Beilstein Journal of Organic Chemistry, 2022)
Indole-3,4- and 4,5-fused carbo- and heterocycles are ubiquitous in bioactive natural products and pharmaceuticals, and hence, a variety of synthetic approaches toward such compounds have been developed. Among these, cyclization and annulation of 3,5-unsubstituted, 4-substituted indoles involving an electrophilic aromatic substitution (SEAr) as the ring closure are particularly attractive, because they avoid the use of 3,4- or 4,5-difunctionalized indoles as starting materials. However, since 3,5-unsubstituted, 4-substituted indoles have two potential ring-closure sites (indole C3 and C5 positions), such reactions in principle can furnish either or both of the indole 3,4- and 4,5-fused ring systems. This Commentary will briefly highlight the issue by summarizing recent relevant literature reports.
Keywords: annulation; cyclization; fused indoles; regioselectivity; SEAr